Measurement and evaluation of the reference service of the National Library Board Singapore - Azizah Sidek (2009)
The Library 2000 report has recommended the setting up of a National Reference Library in Singapore to serve as a reference and information centre to cater to the varied information needs of the population. A study was carried out to measure and evaluate the current reference and information services of the Reference Services Division (RSD) of the National Library Board. In this study, the on-going Wisconsin-Ohio Reference Evaluation Program (WOREP) was used. This program which is being conducted in numerous public and academic libraries in the United States aims at assessing the outcome of reference transactions and identifies factors related to successful and unsuccessful performance. In order to tailor the survey to the local public library's scene, the WOREP's survey instrument was slightly modified. A one-week survey was conducted at RSD, whereby every patron who asked a reference question at the information desk was given a questionnaire at the point when the reference transaction was complete. The focus of this study is to gather data on librarian perception of fill rate or answering success and patron perception of fill rate. From the findings of this survey, the RSD's patron-perceived success rate was not too much different from the WOREP's study of thirty-six public libraries in the United States. The results of the evaluation survey provide reference librarians and managers with information on their question answering success and on factors in the reference situation that are related to answering success. It also identified strengths and weaknesses of the current reference service of RSD.